Gallic acid protects the liver in rats against injuries induced by transient ischemia-reperfusion through regulating microRNAs expressions - Akbari, Ghaidafeh (Iran J Basic Med Sci, 2019)
OBJECTIVE(S): Gallic acid (GA) is a highly effective antioxidant, which its beneficial effects are well known, but its impact on expression of microRNAs (miRs) following hepatic ischemia-reperfusion (I/R) is not well recognized. Therefore, the current research was designed to specify the beneficial effect of GA on miRs (122 and 34a), liver functional tests, and histopathological alterations beyond I/R-induced hepatic injury. MATERIALS AND METHODS: Thirty-two rats were randomly divided into four groups (8 per group) including: sham-operated (S), I/R, and GA+I/R pretreated groups. Rats in sham-operated group received physiologic saline (N/S, 2 ml/kg), on a weekly basis, once a day via intraperitoneally route), then a midline abdominal surgery was performed. IR, and GA+IR pretreated groups received physiologic saline (2 ml/kg), and GA (50, and 100 mg per kg) for same time, IP, respectively, before induction of transient ischemia. One hour after reperfusion, biochemical, and histopathological evaluations were performed and expression of miRs were evaluated. RESULTS: The results showed that GA reduced the concentrations of liver enzymes, miR-122, and miR-34a in serum, and preserved liver cells changes induced by I/R injury. CONCLUSION: These findings showed that GA has beneficial effect on liver damage induced by I/R. Therefore, it is suggested that GA can be administered as an anti-miR before elective hepatic surgeries for prevention of this complication.